ToM & ASD: The interconnection of Theory of Mind with the social-emotional, cognitive development of children with Autism Spectrum Disorder. The use of ICTs as an alternative form of intervention in ASD - Bamicha, Victoria; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Autism Spectrum Disorder is a complex, heterogeneous disorder that affects perception, information processing, social interaction, verbal, and nonverbal communication, and social, and cognitive behavior. Theory of Mind concerns the observation, understanding of mental states, as well as the interpretation of the behaviors that result from them. The present paper focuses on the interconnection of Mind Theory with the social-emotional, and cognitive development of children with Autism Spectrum Disorder. The research findings give prominence to the existence of an interaction between the Theory of Mind and the function of the individual’s social, emotional, and cognitive skills. Therefore, the limited development of Mind Theory observed in children with autism is associated with deficits in their social, cognitive, and metacognitive mechanisms. As a result, the focused holistic approach to their weaknesses in combination with the use of ICTs is a promising, alternative form of therapeutic approach.